"Defending my rights cost me exile". Testimony of Rubí Alondra, a Nicaraguan from Masaya. Issue 3 (2nd September 2021) - Figueroa Romero, Dolores; De Marinis, Natalia
ABSTRACT: This is a testimony given by Rubí Alondra, a citizen of Masaya ( Rubí Alondra is a pseudonym used to protect the personal integrity of the interviewee. Other names that appear in the testimony are also pseudonyms). She joined the civic and neighborhood resistance of her city to support young people who protested the repression of the regime of Daniel Ortega and Rosario Murillo that began in April 2018. Rubí is an example of the thousands of Nicaraguan mothers who participated and helped the popular uprising for several months in 2018.